Dihydroartemisinin, an Anti‐Malaria Drug, Suppresses Estrogen Deficiency‐Induced Osteoporosis, Osteoclast Formation, and RANKL‐Induced Signaling Pathways. (20th January 2016) - Zhou, Lin; Liu, Qian; Yang, Mingli; Wang, Tao; Yao, Jun; Cheng, Jianwen; Yuan, Jinbo; Lin, Xixi; Zhao, Jinmin; Tickner, Jennifer; Xu, Jiake
ABSTRACT: Osteoporosis is an osteolytic disease that features enhanced osteoclast formation and bone resorption. Identification of agents that can inhibit osteoclast formation and function is important for the treatment of osteoporosis. Dihydroartemisinin is a natural compound used to treat malaria but its role in osteoporosis is not known. Here, we found that dihydroartemisinin can suppress RANKL‐induced osteoclastogenesis and bone resorption in a dose‐dependent manner. Dihydroartemisinin inhibited the expression of osteoclast marker genes such as cathepsin K, calcitonin receptor, and tartrate‐resistant acid phosphatase (TRAcP). Furthermore, dihydroartemisinin inhibited RANKL‐induced NF‐κB and NFAT activity. In addition, using an in vivo ovariectomized mouse model, we show that dihydroartemisinin is able to reverse the bone loss caused by ovariectomy. Together, this study shows that dihydroartemisinin attenuates bone loss in ovariectomized mice through inhibiting RANKL‐induced osteoclast formation and function. This indicates that dihydroartemisinin, the first physiology or medicine nobel prize discovery of China, is a potential treatment option against osteolytic bone disease. © 2015 American Society for Bone and Mineral Research.